The Effect Of Reward And Punishment On Employee Performance Is Mediated By Work Motivation At The Sidikalang Sub-District Office - Hairul Anwar Bintang; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2025)
Employee performance is influenced by various factors, including Reward, Punishment, and Work Motivation. This study aims to analyze the effect of Reward and Punishment on Employee Performance by considering work motivation as an intervening variable in the Sidikalang Sub-district Office with a sample of 48 employees. The research uses a quantitative approach with the Partial Least Squares (PLS) method to process survey data from employees. The results showed that Reward had a positive and significant influence on work motivation (T-Statistic 23.965 > 1.96; P-Value 0.000 < 0.05) and indirectly on Employee Performance through Motivation (T-Statistic 3.599 > 1.96; P-Value = 0.001 < 0.05). On the other hand, Punishment does not have a significant influence either directly or indirectly on Employee Motivation or Performance. Work motivation is proven to have a positive and significant influence on Employee Performance (T-Statistic = 3.972 > 1.96; P-Value = 0.000 < 0.05), confirming its important role as a mediating variable in the relationship between Reward and Employee Performance. However, Punishment is not strong enough to affect work motivation or performance directly or indirectly. These findings show that Reward-based strategies are more effective than Punishment-based approaches in improving employee motivation and performance. Institutions are advised to strengthen the Reward system based on performance achievement and provide development opportunities for employees to maximize their potential.